2015
DOI: 10.5709/ce.1897-9254.167
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corporate Social Responsibility on Firms’ Financial Performance in South Africa

Abstract: If Corporate Social Responsibility (CSR) activities are beyond a firm's legal obligations and potentially require a sacrifice in short-term profits, why do firms promote CSR? This question motivates this investigation of the impact of CSR on a firm's Corporate Financial Performance (CFP). This relationship is examined for the period from 2004 to 2013 in South Africa. We assess the short-term impact of CSR announcements on financial returns of firms included in or excluded from the Johannesburg Securities Excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 32 publications
(40 reference statements)
3
63
2
5
Order By: Relevance
“…Similar studies have been carried out in many countries worldwide. In a study focused on Egyptian companies, Hafez (2015) found no impact of CSR on the Þ nancial performance of the banks, which was supported by a study carried out in South Africa (Chetty et al, 2015), which found that CSR activities lead to no signiÞ cant differences in Þ nancial performance. It is fair to say that the evidence is mixed and doesn't provide clear answers.…”
Section: Literature Reviewmentioning
confidence: 74%
“…Similar studies have been carried out in many countries worldwide. In a study focused on Egyptian companies, Hafez (2015) found no impact of CSR on the Þ nancial performance of the banks, which was supported by a study carried out in South Africa (Chetty et al, 2015), which found that CSR activities lead to no signiÞ cant differences in Þ nancial performance. It is fair to say that the evidence is mixed and doesn't provide clear answers.…”
Section: Literature Reviewmentioning
confidence: 74%
“…The following studies reported no evidence for a direct relationship between EP and FP: Aras et al (2010), Jaffe et al (1995), Johnson and Greening (1999), Berman et al (1999), Chetty et al (2015), McWilliams and Siegel (2000), Thornton et al (2003), Elsayed and Paton (2005), and Vogel (2005). These studies generally claim that there is either no relationship between EP and FP, or if there is one, that it is too complex to be found (Margolis and Walsh 2003;Ullmann 1985).…”
Section: Background and Theory On Environmental Performance-firm Perfmentioning
confidence: 94%
“…; Chetty et al . ; Martínez‐Ferrero & Frías‐Aceituno ). Others have called for a focus on specific sectors, such as controversial industries (CIs) (Cai et al .…”
Section: Introductionmentioning
confidence: 99%
“…; Chetty et al . ), and conclusions are currently inconsistent. Only one article has studied the opposite association (CFP → CSP; quadrant [C2] in Table 1) (see Julian & Ofori‐Dankwa ), reporting a negative link, although it does not really measure CSP (as we explain below).…”
Section: Introductionmentioning
confidence: 99%